Pemindahan Ibu Kota Negara Berdasarkan Undang-Undang Nomor 3 Tahun 2022 Tentang Ibu Kota Negara Perspektif Fiqih Siyasah - Yusuf, Syaifullah; Siregar, Deasy Yunita (Asosiasi Ide Bahasa Kepri, 2024)
The National Capital is the center of government and political activities in a country. In Indonesia, plans to move the National Capital have already occurred but have not been implemented. Until the era of President Joko Widodo, this policy was issued again with the enactment of Law Number 3 of 2022 concerning the National Capital. However, this law contains pros and cons, especially in article 6 which regulates the destination location for transferring IKN. This research aims to analyze the provisions and reasons behind the relocation of the National Capital following Law Number 3 of 2022 concerning the National Capital, as well as to find out the views of Fiqh Siyasah regarding the relocation of the National Capital. This research uses normative legal methods which focus on text analysis and library research. With legislation that reviews laws and regulations relating to the transfer of the country's capital. The results of this research indicate that the location of IKN is based on article 6 of Law no. 3 of 2022 concerning the National Capital which is essentially located in East Kalimantan. Then the reason for moving the National Capital is the current objective conditions of the City of Jakarta, namely, urban density, building density, motor vehicle traffic density, natural disasters, the threat of ROB and excessive exploitation of groundwater extraction. In the view of Siyasah Fiqh, moving the National Capital can be justified, as long as it does not violate the people's rights. Because basically the principle of Siyasah Fiqh emphasizes that avoiding harm is better than taking advantage.